Genome-wide meta-analysis of cerebral white matter hyperintensities in patients with stroke. (12th January 2016) - Traylor, Matthew; Zhang, Cathy R.; Adib-Samii, Poneh; Devan, William J.; Parsons, Owen E.; Lanfranconi, Silvia; Gregory, Sarah; Cloonan, Lisa; Falcone, Guido J.; Radmanesh, Farid; Fitzpatrick, Kaitlin; Kanakis, Allison; et al.
Abstract : Objective: For 3, 670 stroke patients from the United Kingdom, United States, Australia, Belgium, and Italy, we performed a genome-wide meta-analysis of white matter hyperintensity volumes (WMHV) on data imputed to the 1000 Genomes reference dataset to provide insights into disease mechanisms. Methods: We first sought to identify genetic associations with white matter hyperintensities in a stroke population, and then examined whether genetic loci previously linked to WMHV in community populations are also associated in stroke patients. Having established that genetic associations are shared between the 2 populations, we performed a meta-analysis testing which associations with WMHV in stroke-free populations are associated overall when combined with stroke populations. Results: There were no associations at genome-wide significance with WMHV in stroke patients. All previously reported genome-wide significant associations with WMHV in community populations shared direction of effect in stroke patients. In a meta-analysis of the genome-wide significant and suggestive loci ( p < 5 × 10 −6 ) from community populations (15 single nucleotide polymorphisms in total) and from stroke patients, 6 independent loci were associated with WMHV in both populations. Four of these are novel associations at the genome-wide level (rs72934505 [ NBEAL1 ], p = 2.2 × 10 −8 ; rs941898 [ EVL ], p = 4.0 × 10 −8 ; rs962888 [ C1QL1 ], p = 1.1 × 10 −8 ; rs9515201 [ COL4A2 ], p = 6.9 × 10 −9 ). Conclusions: Genetic associations with WMHV are shared in otherwise healthy individuals and patients with stroke, indicating common genetic susceptibility in cerebral small vessel disease.